Human dimension and environmental human rights in the international system of the environmental protection - Радзівілл, Олександр Анатолійович; Радзівілл, О. А.; Радзивилл, Александр Анатольевич; Radzivill, Oleksandr A.; Богомазова, Ірина Олександрівна; Богомазова, І. О.; Богомазова, Ирина Александровна; Bohomazova, Iryna O.; Ярошенко, Ірина Станіславівна; Ярошенко, І. С.; Ярошенко, Ирина Станиславовна; Yaroshenko, Iryna S.; et al. (Scientific Association for Research and Strategic Studies Aalborg Academy of Sciences : Denmark, 2020)
The purpose of this research is to identify the patterns and current trends in the formation of human consciousness and environmental human rights in the process of modernizing world civil society in order to form a single international environmental protection system. An important component of the new worldview should also be the noospheric thinking, the main motive of which is the responsible attitude of man towards the future of the planet on the basis of awareness of both the destructive possibilities of modern humanity and the conditionality of its existence for the preservation of a healthy environment. Taking into account the drawbacks of the formation of international law on the basis of exclusively interstate agreements, international law, at the present stage, should actively involve various social groups, social movements, representatives of territorial communities and other subjects of private law relations in making valid decisions, activating their influence on humanization and socialization of activities of the governments, and for states – to develop recommendations for building a new style of relations with their citizens in order to build a single international system of the environment protection.

Метою цього дослідження є виявлення закономірностей та сучасних тенденцій формування людської свідомості та екологічних прав людини в процесі модернізації світового громадянського суспільства з метою формування єдиної міжнародної системи охорони навколишнього середовища. Важливою складовою нового світогляду має бути також ноосферне мислення, головним мотивом якого є відповідальне ставлення людини до майбутнього планети на основі усвідомлення як руйнівних можливостей сучасного людства, так і обумовленості його існування для збереження здорового довкілля. Беручи до уваги недоліки формування міжнародного права на основі виключно міждержавних угод, міжнародне право на сучасному етапі повинно активно залучати різні соціальні групи, соціальні рухи, представників територіальних громад та інших суб'єктів приватноправових відносин до діючих рішень, активізуючи їхній вплив на гуманізацію та соціалізацію діяльності урядів, а для держав - розробляти рекомендації щодо побудови нового стилю відносин зі своїми громадянами з метою побудови єдиної міжнародної системи охорони навколишнього середовища.

Целью данного исследования является выявление закономерностей и современных тенденций в формировании человеческого сознания и экологических прав человека в процессе модернизации мирового гражданского общества с целью формирования единой международной системы защиты окружающей среды. Важной составляющей нового мировоззрения также должно стать ноосферное мышление, основным мотивом которого является ответственное отношение человека к будущему планеты на основе осознания как деструктивных возможностей современного человечества, так и обусловленности его существования для сохранения здоровой окружающей среды. Принимая во внимание недостатки формирования международного права на основе исключительно межгосударственных соглашений, международное право на современном этапе должно активно вовлекать различные социальные группы, общественные движения, представителей территориальных сообществ и других субъектов частноправовых отношений в формирование обоснованных решений, активизирующих их влияние на гуманизацию и социализацию деятельности правительств, а для государств - выработку рекомендаций по построению нового стиля отношений со своими гражданами с целью построения единой международной системы защиты окружающей среды.
Radzivill O. Human dimension and environmental human rights in the international system of the environmental protection / О. Radzivill, I. Bogomazova, I. Yaroshenko, R. Sheludiakov, I. Varava // Journal of Law and Political Sciences. – V. 23 (2). – Scientific Association for Research and Strategic Studies Aalborg Academy of Sciences : Denmark, 2020. – P. 133-174.
Keywords: environmental human rights; global environmental crisis; human consciousness; international environmental protection; world civil society; екологічні права людини; глобальна екологічна криза; свідомість людини; міжнародний захист навколишнього середовища; світове громадянське суспільство; экологические права человека; глобальный экологический кризис; человеческое сознание; международная охрана окружающей среды; мировое гражданское общество; Research Subject Categories::LAW/JURISPRUDENCE